2022
DOI: 10.3389/fcimb.2022.900895
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of neutrophil extracellular traps in fungal infection

Abstract: Fungal infections are global public health problems and can lead to substantial human morbidity and mortality. Current antifungal therapy is not satisfactory, especially for invasive, life-threatening fungal infections. Modulating the antifungal capacity of the host immune system is a feasible way to combat fungal infections. Neutrophils are key components of the innate immune system that resist fungal pathogens by releasing reticular extracellular structures called neutrophil extracellular traps (NETs). When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…NETs are a mechanism to capture and finally kill microorganisms, which is accompanied by simultaneous calprotectin release in a high concentration to support the elimination of the invading pathogens [ 89 ]. This mechanism is well known for host defense against bacteria, and was also recently shown for viruses, such as COVID-19 [ 90 ], and fungi, as shown for the world’s three most deadly fungal pathogens ( C. albicans , Aspergillus fumigatus , and Cryptococcus neoformans ) [ 91 ]. According to the National Nosocomial Infections Surveillance System study, Candida species are responsible for 85% of fungal infections among patients in critical conditions.…”
Section: Zinc and Nutritional Immunitymentioning
confidence: 85%
“…NETs are a mechanism to capture and finally kill microorganisms, which is accompanied by simultaneous calprotectin release in a high concentration to support the elimination of the invading pathogens [ 89 ]. This mechanism is well known for host defense against bacteria, and was also recently shown for viruses, such as COVID-19 [ 90 ], and fungi, as shown for the world’s three most deadly fungal pathogens ( C. albicans , Aspergillus fumigatus , and Cryptococcus neoformans ) [ 91 ]. According to the National Nosocomial Infections Surveillance System study, Candida species are responsible for 85% of fungal infections among patients in critical conditions.…”
Section: Zinc and Nutritional Immunitymentioning
confidence: 85%
“…Innate immune cells can release extracellular structures known as ETs [ 104 ]. Apart from their recognized antibacterial and antimycotic functions [ 105 , 106 ], recent research has unveiled a connection between ET formation and sterile inflammation following tissue damage [ 107 ]. Domer et al demonstrated how ETs could induce further ET formation and establish a positive feedback loop capable of intensifying inflammation [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells can release extracellular structures known as ETs (98). Apart from their recognized bactericidal and anti-fungal functions (99, 100), recent research has unveiled a connection between ET formation and sterile inflammation following tissue damage (101). Domer et al demonstrated how ETs could induce further ET formation and establish a positive feedback loop capable of intensifying inflammation (102).…”
Section: Discussionmentioning
confidence: 99%